Comparison of the air kerma standards of ARPANSA, Australia, and the IAEA in RQR, RQA, and RQT diagnostic X-ray beams - Kam L. Lee; Zakithi Msimang; Duncan Butler; Peter Thomas; Joao Cardoso (Physical and Engineering Sciences in Medicine, 2025)
A comparison of air kerma standards between the Australian Radiation Protection and Nuclear Safety Agency (ARPANSA) and the International Atomic Energy Agency (IAEA) was carried out for the RQR, RQA and RQT radiation qualities (as prescribed by IEC 61267 or IAEA TRS 457) using two ionisation chambers as transfer standards. The ratios between the IAEA and ARPANSA calibration coefficients ranged between 0.993 and 0.997 for RQR beams, 0.990 and 0.999 for RQA beams, and 0.993 to 0.994 for RQT beams. The relative expanded uncertainty for IAEA and ARPANSA was 1.2 and 1.4% respectively, and the comparison results agree at around the level of, or better than, the combined standard uncertainty of 0.74% for all the beams.

Allometric aboveground biomass equations to quantify carbon content of Southeast Australian saltmarsh vegetation - Jami Butler; Clare Duncan; Paul E. Carnell; Anirban Akhand; Stacey M. Trevathan-Tackett; Peter I. Macreadie (Regional Studies in Marine Science, 2025)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Understanding the effects of recreational catch‐and‐release angling on an increasingly important foreign fishing tourism species, the giant African threadfin Polydactylus quadrifilis (Cuvier) - Edward Claude Butler; Amber‐Robyn Childs; Murray Ian Duncan; Warren Mason Potts (Fisheries Management and Ecology, 2020)
Foreign fishing tourism (FFT) is becoming increasingly popular in the developing world, where it often coexists alongside other important sectors involving domestic recreational anglers and dependant artisanal and subsistence fishing communities. Therefore, it is important that FFT operations use effective catch‐and‐release (C&R) angling to minimise negative impacts to locally important fishery species. Using reflex action mortality predictors (RAMPs) and physiological stress indicators, this study assessed the impacts of C&R angling within the FFT fishery targeting Polydactylus quadrifilis (Cuvier) on the Kwanza Estuary, Angola. Air exposure (cumulative link model (CLM): Z = 3.99, p p = 0.02) significantly predicted increased motor impairment. Handling practices were particularly important for larger reproductively valuable individuals as fish size was positively correlated with fight (Spearman's rank: r = 0.85, p r = 0.70, p

Time-course of the physiological-stress response in bronze bream Pachymetopon grande following a simulated catch-and-release angling event - BA Pringle; A-R Childs; EC Butler; AC Winkler; MI Duncan; C Teta; WM Potts (African Journal of Marine Science, 2020)